Antibacterial Potential Of Methanolic Extract Of Cardamom (Elettaria Cardamomum) Pods Against Multidrug Resistant Klebsiella Pneumoniae And Staphylococcus Aureus (Applied Biological Research, 2022)
The unprecedent challenges in the treatment of infectious diseases caused  by the alarming increase of multidrug resistant bacteria are serious concern  worldwide. The present study focused on evaluating the antibacterial  activity of methanolic extract of cardamom (Elettaria cardamomum) pods; and in finding out the minimum inhibitory concentrations (MICs) against  Klebsiella pneumoniae strain MDR and Staphylococcus aureus. The pod  extract was also screened for antioxidant activity. The extract at the  concentrations of 500 and 1000 mg mL-1showed higher zones of growth  inhibition against K. pneumoniaand S. aureus. MICs of K. pneumoniae and  ± 0.01% of reducing power) at the concentration of 1000 µg extract. The study  that the methanolic pod extract of cardamom pods have significant antibacterial potential against MDR pathogens and can be develped astreatment for MDR infections.
Keywords: Antimicrobial resistance; antioxidant activity; cardamom; minimum inhibitor; concentration; multidrug resistance